2018
DOI: 10.31768/2312-8852.2018.40(1):73-78
|View full text |Cite
|
Sign up to set email alerts
|

Variant of Rare Hermansky — Pudlak Syndrome Associated With Granulomatous Colitis: Diagnostics, Clinical Course and Treatment

Abstract: Aim: To study the relationship between the genotype and the phenotype in the patients with Hermansky — Pudlak syndrome (HPS) associated with granulomatous colitis; to monitor clinical course of the disease for adequate treatment, cancer surveillance and genetic counseling. Materials and Methods: The diagnosis of HPS is established by physical examination, chest X-ray, computed tomography, endoscopic examination with biopsy, and laboratory tests, including histology, baseline laboratory blood, urine and feces t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Low vitamin D levels, which may be a factor in HPS subjects avoiding sun exposure, could also contribute to developing colitis (Lozynska et al, 2018).…”
Section: Clinical Management and Therapeutic Aspectsmentioning
confidence: 99%
See 2 more Smart Citations
“…Low vitamin D levels, which may be a factor in HPS subjects avoiding sun exposure, could also contribute to developing colitis (Lozynska et al, 2018).…”
Section: Clinical Management and Therapeutic Aspectsmentioning
confidence: 99%
“…Abnormal endosomal membrane formation was suggested as an underlying cause for HPS colitis leading to ceroid lipofuscin formation, abnormal autophagy and phagocytosis, and inflammation (Felipez et al, 2010; Sofia et al, 2017). It was suggested that the presence of risk alleles in Crohn's disease‐associated genes, like NOD2 or ATG16L1 , in HPS subjects may contribute to developing colitis (Lozynska et al, 2018). Low vitamin D levels, which may be a factor in HPS subjects avoiding sun exposure, could also contribute to developing colitis (Lozynska et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, the estimated prevalence of OCA in the Israeli population is approximately 1 in 10,000 and is caused by several genes including mainly TYR , P , HPS1 , and HPS3 , and even some mutations in HPS4 were described in a patient of Ashkenazi Jewish origin ( Rosenmann et al, 2009 ; Lozynska et al, 2018 ). Founder mutations and additional variants in HPS genes including the newly identified large deletion reported herein in the Ashkenazi Jewish descent underscore the diagnostic possibility of HPS among individuals affected with albinism in Israel.…”
Section: Discussionmentioning
confidence: 99%
“…Immunosuppressants and steroids have no therapeutic effect, and antifibrotic drugs, such as pirfenidone, have shown little efficacy ( 5 ). In contrast, immunosuppressants, such as rituximab, are effective against granulomatous colitis, which is one of its complications ( 6 , 7 ).…”
Section: Introductionmentioning
confidence: 99%